Creating a middle-class culture: Arthur Bestor and adult education in transition - Amy D. Rose (Adult Education Research Conference, 1994)
This paper analyzes the work of Arthur Bestor, President Chautauqua Institution in the first half of the twentieth century. It discusses Bestor's view of the changing nature of adult education and examines his speeches and writings in order to understand how this work fit into what historian Joan Shelley Rubin calls middlebrow culture.